(untitled) (Physical Education, Health and Social Sciences, 2026)
To discover "difficult circumstances associated with education in Pakistani higher learning institutions," all of the research used in this study was exploratory in nature. The employment of exploratory research methodologies allows for faster and less expensive research goals achievement. Pakistan has recently had to deal with a number of issues related to education, including curriculum, the demise of institutions of learning, corruption in the field of education, the conduct of teachers, and a dearth of research. The current issue with education, which economies require to develop and operate, is a fall in educational institutions and a move to research. Our study attempts to pinpoint the most prevalent issues that Pakistani schools have faced lately. Triangulation was employed by the researchers to confirm the precision and reliability of the recorded data. The researchers employed controlled interviews, researcher-conducted surveys, and researcher-conducted questionnaires in this triangulation. Researchers from five chosen universities completed the first set of data on this, which was gathered from instructors and students by a centralized group using a template consisting of 100 questionnaires per university. The advancement of Pakistan greatly depends on this study initiative. The standard of classroom instruction is the dependent variable in this curriculum, whereas the independent factors include educational corruption, the collapse of educational organizations, the degradation of teacher conduct, and the learning image. The research suggested to increase literacy, the Pakistani government made compulsory schooling a requirement for all people under the compulsory age of sixteen, revise the courses needed for expert consultation and researcher training, provide all educators with training on accepting individual and group accountability and especially those at the higher education level—need to quicken the speed of their college-focused coaching and learning initiatives. Therefore, the government needs to provide the Commission on Higher Education (HEC) greater funding.